Building connected communities of care : the playbook for streamlining effective coordination between medical and community-based organizations - Kosel, Keith; Miff, Steve (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
As a community, aligning efforts across a community to support the safety and well-being of vulnerable and underserved individuals is extraordinarily difficult. These individuals suffer disproportionally from health issues, job loss, a lack of stable housing, high utility costs, substance abuse, and homelessness. In addition to medical care, these individuals often critically need access to community social sector organizations that provide a distinct and complementary set of services, such as housing, food services, emergency utility assistance, and employment assistance. These services are just as vital as healthcare services to these individuals' long-term health and well-being, with data suggesting that 80-90% of health outcomes can be attributed to factors beyond direct medical intervention. This book proposes a novel approach to the coordination of medicine and social services through the use of people, process, and technology, with the goal being to streamline coordination between medical and Community-Based Organizations and to promote true cross-sector patient and client advocacy. The book is based on the experience of Dallas, TX, which was one of the first metropolitan regions to develop a comprehensive foundation for partnership between a community's clinical and social sectors using web-based information exchange. In the 5 years since the initial launch, the authors have been able to provide seamless connection, communication, and coordination between healthcare providers and a wide array of community-based social service organizations (a/k/a Community-Based Organizations or CBOs), criminal justice entities, and various other community organizations, including non-collegiate educational systems. This practical how-to guide is the codification of transferrable lessons from successes and challenges faced when working with clinical, community, and government leaders. By reading this playbook, leaders interested in building (or expanding) connected clinical-community services will learn how to: 1) facilitate cross-sector care coordination; 2) enable community care partners to better provide targeted services to community residents; 3) reduce duplication of services across partnering organizations; and 4) help to bridge service gaps in the currently fragmented system. Implementation of services, as recommended in this book, will ultimately streamline assistance efforts, reduce repeat crises and emergency funding requests, help address disparities of care, and improve the health, safety, and well-being of the most vulnerable community residents.
The Call to Action. Foreword. Preface. Contributors. About the Authors. List of Commonly Used Abbreviations. 1 Playbook Overview. 2 The Readiness Assessment. 3 Governance Track. 4 Legal/Policy Track. 5 Technology Platform Track. 6 Clinical Providers Track. 7 Community Partners Track. 8 Program Sustainability Track. 9 Final Notes. Key Documents. References. Index.
"A Productivity Press book."
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / Administration; MEDICAL / Health Care Delivery; Community health services -- Planning; Community health services -- Management; Community health services -- Administration